LANGUAGE EXPRESSIONS IN CONSTRUCTING PHYSICAL MASCULINITY IN INDONESIAN TEEN LIT - Azizatuz Zahro; Anang Santoso; Dawud Dawud (Fakultas Sastra Universitas Negeri Malang, 2020)
LANGUAGE EXPRESSIONS IN CONSTRUCTING PHYSICAL MASCULINITY IN INDONESIAN TEEN LITAbstract: Teen lit serves a central position in the conception of masculinity in teenagers due to its closeness to them as readers. For teenagers, physical masculinity is relatively highlighted compared to masculinity in other dimensions. Physical masculinity is expressed through classic names, which is related to strength, and is signified by ‘provincial’ names. Physical masculinity is also conveyed through the expressions of the eyes and figures. Besides, a specific cultural icon typically related to handsomeness is also used to construct physical masculinity in teen lit. Keywords: Language expression, Physical masculinity, Teen lit, Construction, Gender identityEKSPRESI BAHASA DALAM PEMBANGUNAN MASKULINITAS FISIK PADA SASTRA REMAJA INDONESIAAbstrak: Sastra remaja memiliki posisi sentral dalam konsepsi maskulinitas pada remaja karena kedekatan dengan mereka sebagai pembaca. Pada masa remaja, maskulinitas fisik relatif lebih menonjol dibandingkan dengan maskulinitas pada dimensi lain. Maskulinitas fisik diekspresikan melalui nama klasik, yang dihubungkan dengan kekuatan, dan secara negatif dikonotasikan dengan nama yang “udik”. Maskulinitas fisik juga ditunjukkan melalui ekspresi mata dan figur. Selain itu, ikon budaya tertentu yang biasanya terkait dengan ketampanan juga digunakan untuk membangun maskulinitas fisik dalam seni remaja.Kata kunci: Ekspresi bahasa, Maskulinitas fisik, Sastra remaja, Konstruksi, Identitas gender Permalink/DOI: dx.doi.org/10.17977/um015v48i22020p131